Sie sind auf Seite 1von 19

APPENDIX

CN Complex Numbers

„ Complex Plane

The complex numbers 3 + 3i , 4i, 2, and 1 − i are Im(z )


1. 4
(0, 4)
plotted as the respective points ( 3, 3) , ( 0, 4 ) ,
(3, 3)
( 2, 0 ) , and (1, − 1) in the complex plane (see
figure). (2, 0)
Re(z )
–4 4
(1, –1)

–4

„ Complex Operations
2. (a) ( 2 + 3i )( 4 − i ) = 8 − 2i + 12i − 3i 2 = 11 + 10i
(b) ( 2 + 3i )(1 + i ) = 2 + 2i + 3i + 3i 2 = −1 + 5i
(c) Rationalizing the denominator, multiply the numerator and denominator by 1 − i yielding
1 1− i 1− i 1 i
= = − .
1+ i 1− i 2 2 2

(d) Rationalizing the denominator, we multiply the numerator and denominator by 3 − i


yielding
2+i 3−i 7 +i 7 i
= = + .
3+i 3−i 10 10 10

„ Complex Exponential Numbers

3. (a) Using Euler’s formula, we write


e2π i = cos 2π + i sin 2π = 1 + i ( 0 ) = 1 .

916
SECTION CN Complex Numbers 917

(b) Using Euler’s formula, we write


π π
eiπ 2 = cos + i sin = 0 + i (1) = i .
2 2

(c) Using Euler’s formula, we write


e −iπ = cos ( −π ) + i sin ( −π ) = cos π − i sin π = −1 .

(d) Using the property e a + b = ea eb and using Euler’s formula, we write

⎛ π π⎞ ⎛ 2 2⎞ 2 2 2
e(
2 +π i 4 )
= e 2 eπ i 4 = e2 ⎜ cos + i sin ⎟ = e2 ⎜ +i ⎟⎟ = e + ie2 .
4 4⎠ ⎜
⎝ ⎝ 2 2 ⎠ 2 2

„ Magnitudes and Angles

4. (a) Absolute value:

1 + 2i = 12 + 22 = 5 .

2 63
Polar angle: θ = tan −1 ≈ 63° or roughly π radians.
1 180

(b) Absolute value:

−i = 02 + ( −1) = 1 .
2

Polar angle: The complex number –i is located at the point ( 0, − 1) in the complex plane

so the angle is radians (or 270°).
2

(c) Absolute value:

−1 − i = ( −1)2 + ( −1)2 = 2.

Polar angle: θ = π + tan −1 (1) and because the number −1 − i is in the third quadrant in

the complex plane, we have θ = radians (or 225°).
4

(d) Absolute value:

−2 + 3i = ( −2 )2 + 33 = 13 .

⎛ 3⎞ 124
Polar angle: θ = π − tan −1 ⎜ − ⎟ ≈ 124° or π radians.
⎝ 2⎠ 180

(e) e 2i . We write the exponential as

e 2i = cos 2 + i sin 2 .
918 APPENDIX

Magnitude is

e 2i = cos 2 + i sin 2 = cos 2 2 + sin 2 2 = 1 .

Polar angle is
⎛ sin 2 ⎞
θ = tan −1 ⎜ ⎟ = tan −1 ( tan 2 ) = 2 .
⎝ cos 2 ⎠
2+i
(f) . We rationalize the denominator to get
1+ i
2 + i 1− i 3 i
= − .
1+ i 1− i 2 2

Magnitude is
2 2
2+i ⎛3⎞ ⎛ 1⎞ 1
= ⎜ ⎟ +⎜− ⎟ = 10 .
1+ i ⎝2⎠ ⎝ 2⎠ 2

Polar angle is
⎛ 1⎞
θ = tan −1 ⎜ − ⎟ ≈ −18.4°
3
⎝ ⎠

or 341.6°.

„ Complex Verification I

5. We check the first root z = −1 + i by direct substitution:

( −1 + i )2 + 2 ( −1 + i ) + 2 = 1 − 2i − 1 − 2 + 2i + 2 = 0 .
The second root −1 − i is left to the reader.

„ Complex Verification II

6. By direct substitution we have


4
⎛1+ i ⎞

⎝ 2 ⎠
1
4
1
4
2 2 1
4
1 2
⎟ = (1 + i ) = (1 + i ) (1 + i ) = (1 + 2i − 1)(1 + 2i − 1) = 4i = −1 .
4

4
( )
„ Real and Complex Parts

7. Calling the complex number z = a + ib , we write

( )
z 2 + 2 z = ( a + ib ) + 2 ( a + ib ) = a 2 − b 2 + 2iab + 2 ( a + ib )
2

.
( )
= a 2 − b 2 + 2a + i ( 2ab + 2b )

(a) ( )
Re z 2 + 2 z = a 2 − b 2 + 2a (b) ( )
Im z 2 + 2 z = 2b ( a + 1)
SECTION CN Complex Numbers 919

„ Absolute Value Revisited


8. Using the formula z = zz , yields

4 + 2i = ( 4 + 2i )( 4 − 2i ) = 16 + 4 = 2 5 .

„ Roots of Unity

9. The m roots of z m = 1 (called the roots of unity) are the m values


⎛ ⎛ 2π k ⎞ ⎛ 2π k ⎞ ⎞
zk = 11 m ⎜ cos ⎜ ⎟ + i sin ⎜ ⎟ ⎟ , k = 0,1 " m − 1 .
⎝ ⎝ m ⎠ ⎝ m ⎠⎠

Note that for z = 1 yields polar angle θ = 0 for the previous formula.

(a) z 2 = 1 has two roots


⎛ 2π k ⎞ ⎛ 2π k ⎞
zk = cos ⎜
2 ⎟ + i sin ⎜ 2 ⎟ = cos (π k ) + i sin (π k ) ,
⎝ ⎠ ⎝ ⎠

k = 0 , 1 or z = ±1 .

(b) z 3 = 1 has three roots


⎛ 2π k ⎞ ⎛ 2π k ⎞
zk = cos ⎜ ⎟ + i sin ⎜ ⎟,
⎝ 3 ⎠ ⎝ 3 ⎠

k = 0 , 1, 2 or
z1 = +1
⎛ 2π ⎞ ⎛ 2π ⎞ 1 3
z2 = cos ⎜ ⎟ + i sin ⎜ ⎟=− + i
⎝ 3 ⎠ ⎝ 3 ⎠ 2 2
⎛ 4π ⎞ ⎛ 4π ⎞ 1 3
z3 = cos ⎜ ⎟ + i sin ⎜ ⎟=− − i.
⎝ 3 ⎠ ⎝ 3 ⎠ 2 2

(c) z 4 = 1 has four roots


⎛ 2π k ⎞ ⎛ 2π k ⎞
zk = cos ⎜ ⎟ + i sin ⎜ ⎟,
⎝ 4 ⎠ ⎝ 4 ⎠

k = 0 , 1, 2, 3 or
z1 = 1
z2 = i
z3 = −1
z 4 = −i .
920 APPENDIX

„ Derivatives of Complex Functions

10. By direct differentiation we have


(a) F ( t ) = e( )
1−i t (b) F ( t ) = e3it

F ′ ( t ) = (1 − i ) e( )
1−i t F ′ ( t ) = 3ie3it

F ′′ ( t ) = (1 − i ) e( ) = −2ie( )
2 1− i t 1−i t F ′′ ( t ) = −9e3it

F ( t ) = e(
(c) 2 + 3i ) t

F ′ ( t ) = ( 2 + 3i ) e(
2 + 3i )t

F ′′ ( t ) = ( −5 + 12i ) e(
2 + 3i )t

„ Real and Complex Parts of Exponentials

11. We write each of the following complex numbers in a + bi form.


⎛ π π⎞
e(
1+π i )
e(
2 +π i 2 )
(a) = e1 ( cos π + i sin π ) = −e (b) = e 2 ⎜ cos + i sin ⎟ = ie 2
⎝ 2 2⎠

(c) eπ i = cos π + i sin π = −1

(d) e−π i = cos ( −π ) + i sin ( −π ) = cos π − i sin π = −1

„ Complex Exponential Functions

12. We use the properties of exponentials and Euler’s formula to write

e(
−1+ 2 i )t
(a) e 4π it = cos ( 4π t ) + i sin ( 4π t ) (b) = e −t e 2it = e −t ( cos 2t + i sin 2t )

„ Using deMoivre’s Formula

Following the procedures in Example 7 we obtain the following:


3t 3t
13. y (t ) = c1e−t + c2 et / 2 sin + c3et / 2 cos
2 2
3 2t 3 2t 3 2t 3 2t
14. y (t ) = c1e −3 2t/2
sin − c2 e3 2t/2
sin + c3e −3 2t/2
cos + c4 e3 2t/2
cos
2 2 2 2
SECTION LT Linear Transformations 921

LT Linear Transformations

„ Coordinate Map

1. { }
Let b1 , b2 , " , bn be a basis for V and [ v ]B : V → R n be the mapping that assigns to each of
K K
the vectors u and v in V their coordinate vectors

⎡ α1 ⎤ ⎡ β1 ⎤
⎢α ⎥ ⎢β ⎥
K ⎢ 2⎥ K
uB = and v B = ⎢ 2 ⎥ .
⎢# ⎥ ⎢# ⎥
⎢ ⎥ ⎢ ⎥
⎣α n ⎦ ⎣βn ⎦
K K
We wish to prove linearity for u and v in V,

⎡ α1 ⎤ ⎡ β1 ⎤ ⎡ α1 + β1 ⎤
⎢α ⎥ ⎢ β ⎥ ⎢α + β ⎥
[uK ]B + [ vK ]B = ⎢⎢ #2 ⎥⎥ + ⎢⎢ #2 ⎥⎥ = ⎢⎢ 2 # 2 ⎥⎥ = [uK + vK ]B .
⎢ ⎥ ⎢ ⎥ ⎢ ⎥
⎣α n ⎦ ⎣ β n ⎦ ⎣α n + β n ⎦
K K K
Also for any constant c and v in V, [ cv ]B = c [ v ]B by a similar coordinate-wise argument.

„ Isomorphisms
2. Some examples are R 4 , C 4 , and P3 .

„ Isomorphism Subtleties
3. M12 ( R ) = {[ a b ]: a, b ∈ R} so the elements of M12 ( R ) are not elements of

⎧⎪ ⎡ a b ⎤ ⎫⎪
M 22 ( R ) = ⎨ ⎢ ⎥ : a , b, c , d ∈ R ⎬ .
⎪⎩ ⎣ c d ⎦ ⎭⎪
⎧⎪ ⎡ a b ⎤ ⎫⎪
Thus M12 ( R )is not a subspace. However T : M12 ( R ) → ⎨ ⎢ ⎥ : a, b ∈ R ⎬ is an
⎩⎪ ⎣ 0 0 ⎦ ⎭⎪
isomorphism to a subspace of M 22 ( R ) .

„ Isomorphisms Have Inverses


K K
4. Let T : V → W be an isomorphism. Define T −1 : W → V so that T −1 ( w ) = v if and only if
K K
T ( v) = w .
K K K K
Because T is surjective, for each w in W, there is at least one v in V such that T ( v ) = w .
K K K K
Because T is injective, for each w in W, there is exactly one v in V such that T ( v ) = w .

Show that T −1 is linear, injective and surjective.


922 APPENDIX
K K K K
Linearity: Suppose w1 and w 2 are vectors in W so that T −1 ( w1 ) = v1 and
K K K K K K K K
T −1 ( w 2 ) = v 2 . Now T ( v1 + v 2 ) = T ( v1 ) + T ( v 2 ) = w1 + w 2 because T is linear. Therefore
K K K K K K
T −1 ( w1 + w 2 ) = v1 + v 2 = T −1 ( w1 ) + T −1 ( w 2 ) .
K K K K K K
Also for any constant c, T ( cv1 ) = cT ( v1 ) = cw1 so that T −1 ( cw1 ) = cv1 = cT −1 ( w1 ) .
K K K K K
Injectivity: Suppose T −1 ( w1 ) = T −1 ( w 2 ) for some vectors w1 and w 2 in W , and let v1
K K K K K
and v 2 be their respective image vectors. Because v1 = v 2 and T is a function, T ( v1 ) = T ( v 2 ) ,
K K
so that w1 = w 2 .
K K K K
Surjectivity: Suppose v is any vector in V . Then T ( v ) = w for some w in W , so that
K K
T −1 ( w ) = v .

„ Composition of Isomorphisms
G G G
5. {
T : V → W is an isomorphism and b1 , b 2 , ", b n } is a basis for V . We want to show that
G G G
{( ) ( ) ( )}
T b1 , T b 2 , ", T b n is a basis for W .
K K K K
Span: Suppose that w is a vector in W . Then T ( u ) = w for some u in V because T is
K G G G
surjective. Then we can write u = β1b1 + β 2b 2 + " + β n b n for some constants β1 , β 2 , ", β n .
G G G G G G
G G
( ) ( ) ( )
w = T ( u ) = T β1b1 + β 2b 2 +" + β n b n = β1T b1 + β 2T b 2 + " + β nT b n . ( )
G G G
{( ) ( )
So T b1 , T b 2 , ", T b n ( )} spans W .
Linear Independence:
G G G G
( ) ( ) ( )
Suppose c1T b1 + c2T b 2 +" + cnT b n = 0 for some constants c1 , c2 , ", cn .
G G G G G
Then (
G
)
T c1b1 + c2b 2 + " + cn b n = 0 = T 0 because () T is linear;
G G G
c1b1 + c2b 2 + " + cn b n = 0 because T is injective.
G G G
{ }
However because b1 , b 2 , ", b n is a basis and hence linearly independent,
G G G
{( ) ( ) ( )}
c1 = c2 =" = cn = 0 , so that T b1 , T b 2 , ", T b n is linearly independent.
G G G
By the two properties shown, {T ( b ) , T ( b ) , ", T ( b )} is a basis for W .
1 2 n

„ Isomorphisms and Bases

6. From Problem 30 in Section 5.1, we know that the composition of linear transformation is linear.
We use the functions L : U → V and T : V → W to prove the following general results about
the composition of functions T D L : U → W .
SECTION LT Linear Transformations 923

The composition of injective functions is injective.

Suppose
G G
T D L ( u1 ) = T D L ( u 2 )

for some u1 and u 2 in U . Then


G G
T ( L ( u1 ) ) = T ( L ( u 2 ) ) ,
G G G G
so that L ( u1 ) = L ( u 2 ) since T is injective. Also, u1 = u 2 since L is injective. Therefore T D L is
injective.

The composition of surjective functions is surjective.

Suppose
G
w∈W .
G G G G G
Because T is surjective, T ( v ) = w for some v in V. Also, because L is surjective, L ( u ) = v for
G G G G G
some in u . Therefore, T D L ( u ) = T ( L ( u ) ) = T ( v ) = w .

We have proved that the composition of surjective functions is surjective.

We know that L : U → V and T : V → W are isomorphisms if and only if they are


injective and surjective linear transformations, so that T D L must also have those properties.

„ Associated Matrices
7. Given T : R 2 → R3 such that T ( x, y ) = ( 2 x − y, x, y ) . B and C are the standard bases for R 2
and R 3 , respectively
⎡ ⎡ 2 ⎤ ⎡ −1⎤ ⎤ ⎡ 2 −1⎤
G G ⎢ ⎥
M B = ⎡⎣T ( e1 ) ⎤⎦ ⎡⎣T ( e2 ) ⎤⎦ = ⎢ ⎢⎢ 1⎥⎥ ⎢⎢ 0 ⎥⎥ ⎥ = ⎢⎢ 1 0 ⎥⎥
⎡ ⎤
⎣ c c ⎦
⎢ ⎢⎣ 0 ⎥⎦ ⎢⎣ 1⎥⎦ ⎥ ⎢⎣ 0 1⎥⎦
⎣ ⎦

8. { }
G G G
Given T : P2 → R 3 where B = t 2 , t , 1 and C = {e1 , e2 , e3 } , the standard basis for R 3 , and

( ) ( )
where T at 2 + bt + c = aT t 2 + bT ( t ) + cT (1) = ( a − b, a, 2c ) .

⎡ ⎡ 1⎤ ⎡ −1⎤ ⎡ 0 ⎤ ⎤ ⎡ 1 −1 0 ⎤
⎢ ⎥

⎣⎢ ⎣
2
⎦c( )
M B = ⎡T t ⎤ ⎡⎣T ( t ) ⎤⎦ ⎡⎣T (1) ⎤⎦ = ⎢ ⎢⎢ 1⎥⎥ ⎢⎢ 0 ⎥⎥ ⎢⎢ 0 ⎥⎥ ⎥ = ⎢⎢ 1 0 0 ⎥⎥ .
c


c⎦
⎢ ⎢⎣ 0 ⎥⎦ ⎢⎣ 0 ⎥⎦ ⎢⎣ 2 ⎥⎦ ⎥ ⎢⎣ 0 0 2 ⎥⎦
⎣ ⎦
924 APPENDIX

⎡ a b ⎤ ⎡ 2a c + b ⎤
9. T⎢ ⎥=⎢ ⎥,
⎣ c d ⎦ ⎣ c + b 2d ⎦
⎡⎛ 1 0 ⎞ ⎛ ⎡0 1 ⎤ ⎞ ⎛ ⎡0 0⎤ ⎞ ⎛ ⎡0 0⎤ ⎞ ⎤
⎡ ⎤
M B = ⎢⎜⎜ T ⎢ ⎟ ⎜⎜ T ⎢ ⎥ ⎟⎟ ⎜⎜ T ⎢ ⎥ ⎟⎟ ⎜⎜ T ⎢ ⎥
⎥ ⎟⎟ ⎥
⎢⎝ ⎣0 0 ⎦⎥ ⎠⎟ ⎝ ⎣ 0 0 ⎦ ⎠c ⎝ ⎣1 0 ⎦ ⎠c ⎝ ⎣ 0 1 ⎦ ⎠c ⎦
⎣ c

⎡ ⎡ 2⎤ ⎡0⎤ ⎡0⎤ ⎡ 0⎤ ⎤ ⎡ 2 0 0 0⎤
⎢⎢ ⎥ ⎢ ⎥ ⎢ ⎥ ⎢ ⎥ ⎥ ⎢
0 1 1 0 0 1 1 0⎥⎥
= ⎢⎢ ⎥ ⎢ ⎥ ⎢ ⎥ ⎢ ⎥ ⎥ = ⎢ .
⎢ ⎢ 0 ⎥ ⎢ 1⎥ ⎢ 1⎥ ⎢ 0⎥ ⎥ ⎢ 0 1 1 0⎥
⎢⎢ ⎥ ⎢ ⎥ ⎢ ⎥ ⎢ ⎥ ⎥ ⎢ ⎥
⎣⎢ ⎣ 0 ⎦ ⎣ 0 ⎦ ⎣0 ⎦ ⎣ 2⎦ ⎦⎥ ⎣ 0 0 0 2⎦

⎡ Tr ( A ) 0 ⎤ ⎡a b ⎤ ⎡a + d 0 ⎤
10. V = W = M 22 [ R ] , T ( A ) = ⎢ ⎥ . We can write T ⎢ ⎥=⎢ . B and C
⎣ 0 Tr ( A ) ⎦ ⎣c d ⎦ ⎣ 0 a + d ⎥⎦

are the same as the bases in Problem 9.


⎡⎛ 1 0 ⎞ ⎛ ⎡0 1 ⎤ ⎞ ⎛ ⎡0 0⎤ ⎞ ⎛ ⎡0 0⎤ ⎞ ⎤
⎡ ⎤
M B = ⎢⎜⎜ T ⎢ ⎟ ⎜⎜ T ⎢ ⎥ ⎟⎟ ⎜⎜ T ⎢ ⎥ ⎟⎟ ⎜⎜ T ⎢ ⎥ ⎟⎟

⎢⎝ ⎣0 0 ⎦⎥ ⎠⎟ ⎝ ⎣ 0 0 ⎦ ⎠c ⎝ ⎣1 0 ⎦ ⎠c ⎝ ⎣ 0 1 ⎦ ⎠c ⎦⎥
⎣ c

⎡ ⎡ 1⎤ ⎡ 0 ⎤ ⎡0 ⎤ ⎡ 1⎤ ⎤ ⎡ 1 0 0 1⎤
⎢⎢ ⎥ ⎢ ⎥ ⎢ ⎥ ⎢ ⎥ ⎥ ⎢
0 0 0 0 0 0 0 0 ⎥⎥
= ⎢⎢ ⎥ ⎢ ⎥ ⎢ ⎥ ⎢ ⎥ ⎥ = ⎢ .
⎢ ⎢0⎥ ⎢0⎥ ⎢0⎥ ⎢0⎥ ⎥ ⎢0 0 0 0⎥
⎢⎢ ⎥ ⎢ ⎥ ⎢ ⎥ ⎢ ⎥ ⎥ ⎢ ⎥
⎣⎢ ⎣ 1⎦ ⎣ 0 ⎦ ⎣0 ⎦ ⎣ 1⎦ ⎦⎥ ⎣ 1 0 0 1⎦

11. { }
B = C = e −2t , te −2t . T ( f ) = f ′ − f so that

( ) ( ( ) (
T ae −2t + bte−2t = a −2e −2t + b e −2t − 2te −2t )) − ( ae −2 t
)
+ bte −2t = ( −3a + b ) e −2t + ( −3b ) te−2t

and
⎡ ⎤

( ( )) (T (te )) ⎦⎤⎥ = ⎢⎣ ⎡⎢⎣−03⎤⎥⎦ ⎡⎢⎣−31⎤⎥⎦ ⎥⎦ = ⎡⎢⎣−03
M B = ⎡⎢ T e −2t
c
−2 t
c
1⎤
−3⎥⎦
.

„ Changing Bases
⎧⎪ ⎡1⎤ ⎡ 3⎤ ⎫⎪ ⎧⎪ ⎡ −1⎤ ⎡ 0 ⎤ ⎫⎪
12. V = M 21 ( R ) , B = ⎨ ⎢ ⎥ , ⎢ ⎥ ⎬ , C = ⎨ ⎢ ⎥ , ⎢ ⎥ ⎬ ,
⎪⎩ ⎣1⎦ ⎣ 0 ⎦ ⎪⎭ ⎪⎩ ⎣ 1⎦ ⎣ 2 ⎦ ⎭⎪
⎛ ⎡1⎤ ⎞ ⎡1⎤ ⎛ ⎡ −1⎤ ⎡ 0⎤ ⎞ ⎡c ⎤
id ⎜⎜ ⎢ ⎥ ⎟⎟ = ⎢ ⎥ = ⎜⎜ c1 ⎢ ⎥ + c2 ⎢ ⎥ ⎟⎟ c = ⎢ 1 ⎥
⎝ ⎣1⎦ ⎠ ⎣1⎦ ⎝ ⎣ 1⎦ ⎣ 2⎦ ⎠ ⎣ c2 ⎦
⎛ ⎡ 3⎤ ⎞ ⎡ 3⎤ ⎛ ⎡ −1⎤ ⎡ 0⎤ ⎞ ⎡d ⎤
id ⎜⎜ ⎢ ⎥ ⎟⎟ = ⎢ ⎥ = ⎜⎜ d1 ⎢ ⎥ + d 2 ⎢ ⎥ ⎟⎟ c = ⎢ 1 ⎥ .
⎝ ⎣ 0 ⎦ ⎠ ⎣ 0 ⎦ ⎝ ⎣ 1⎦ ⎣ 2⎦ ⎠ ⎣d2 ⎦
To find c1 and c2 :
⎡1⎤ ⎡ −1⎤ ⎡ 0⎤
⎢1⎥ = c1 ⎢ 1⎥ + c2 ⎢ 2 ⎥ ,
⎣⎦ ⎣ ⎦ ⎣ ⎦
SECTION LT Linear Transformations 925

1 = −c1 + 0c2 so c1 = −1 and 1 = 1c1 + 2c2 so c2 = 1 . To find d1 and d 2 :

⎡ 3⎤ ⎡ −1⎤ ⎡ 0⎤
⎢ 0 ⎥ = d1 ⎢ 1⎥ + d 2 ⎢ 2 ⎥ ,
⎣ ⎦ ⎣ ⎦ ⎣ ⎦
3
3 = −1d1 + 0d 2 so d1 = −3 and 0 = 1d1 + 2d 2 so d 2 = ;
2
⎡ −1 −3⎤
MB = ⎢ ⎥.
⎢ 1 3⎥
⎣⎢ 2 ⎥⎦

13. { } { }
V = P3 , B = t 3 , t 2 , t ,1 , C = 2t , t 3 , t − t 2 , 5 ,

⎡ a1 ⎤
⎢a ⎥
( ) ( ( )
⎡id t 3 ⎤ = a1 ( 2t ) + a2t 3 + a3 t − t 2 + a4 ( 5 )
⎣ ⎦c ) c
= ⎢ 2⎥ .
⎢ a3 ⎥
⎢ ⎥
⎣ a4 ⎦

We equate coefficients of like terms to find a1 , a2 , a3 , a4 :

( )
t 3 = a1 ( 2t ) + a2t 3 + a3 t − t 2 + a4 ( 5 ) .

The coefficient of t 3 is 1 = a2 . The coefficient of t 2 is 0 = − a3 . The coefficient of t is


0 = 2a1 + a3 , and the coefficient of 1 is 0 = 5a4 so that

⎡ a1 ⎤ ⎡0 ⎤
⎢ a ⎥ ⎢ 1⎥
⎢ 2⎥ = ⎢ ⎥
⎢ a3 ⎥ ⎢0 ⎥
⎢ ⎥ ⎢ ⎥
⎣ a4 ⎦ ⎣0 ⎦

and
⎡ b1 ⎤
⎢b ⎥
( ) ( ( )
⎡id t 2 ⎤ = b1 ( 2t ) + b2t 3 + b3 t − t 2 + b4 ( 5 )
⎣ ⎦c ) c
= ⎢ 2⎥ .
⎢ b3 ⎥
⎢ ⎥
⎣b4 ⎦
⎡ 1⎤
⎡ b1 ⎤ ⎢ ⎥
⎢b ⎥ ⎢ 2 ⎥
We equate coefficients of like terms again to find ⎢ 2 ⎥ = ⎢ 0 ⎥ and
⎢ b3 ⎥ ⎢ ⎥
⎢ ⎥ ⎢ −1⎥
⎣b4 ⎦ ⎢ 0 ⎥
⎣ ⎦
926 APPENDIX

⎡ c1 ⎤
⎢c ⎥
( ( )
⎡⎣id ( t ) ⎤⎦ = c1 ( 2t ) + c2t 3 + c3 t − t 2 + c4 ( 5 )
c ) c
= ⎢ 2⎥ .
⎢ c3 ⎥
⎢ ⎥
⎣ c4 ⎦

Obtaining
⎡1⎤
⎡ c1 ⎤ ⎢ ⎥
⎢c ⎥ ⎢ 2 ⎥
⎢ 2 ⎥ = ⎢ 0⎥
⎢ c3 ⎥ ⎢ ⎥
⎢ ⎥ ⎢ 0⎥
⎣ c4 ⎦ ⎢ 0 ⎥
⎣ ⎦

and
⎡ d1 ⎤
⎢d ⎥
( ( )
⎡⎣id (1) ⎤⎦ = d1 ( 2t ) + d 2t 3 + d3 t − t 2 + d 4 ( 5 )
c ) c
= ⎢ 2⎥ .
⎢ d3 ⎥
⎢ ⎥
⎣d4 ⎦

We then get
⎡ 0⎤
⎡ d1 ⎤ ⎢ ⎥
⎢d ⎥ ⎢ 0⎥
⎢ 2 ⎥ = ⎢ 0⎥
⎢ d3 ⎥ ⎢ ⎥
⎢ ⎥ ⎢1 ⎥
⎣d4 ⎦ ⎢ ⎥
⎣5⎦

and
⎡ 1 1 ⎤
⎢0 2 2 0⎥
⎢ ⎥
⎢ 1 0 0 0⎥
MB = ⎢ .
0 −1 0 0 ⎥
⎢ ⎥
⎢ 1⎥
⎢⎣ 0 0 0 5 ⎥⎦

⎧⎪ ⎡ 1 0 ⎤ ⎡0 1⎤ ⎡0 0 ⎤ ⎡ 0 0⎤ ⎫⎪ ⎧⎪ ⎡ 1 0 ⎤ ⎡ 1 1⎤ ⎡1 1⎤ ⎡1 1⎤ ⎫⎪
14. V = M 22 ( R ) , B = ⎨ ⎢ ⎥ , ⎢ ⎥ , ⎢ ⎥ , ⎢ ⎥ ⎬ , C = ⎨⎢ ⎥, ⎢ ⎥, ⎢ ⎥, ⎢ ⎥⎬ .
⎪⎩ ⎣ 0 0 ⎦ ⎣0 0 ⎦ ⎣ 1 0 ⎦ ⎣ 0 1⎦ ⎪⎭ ⎩⎪ ⎣0 0 ⎦ ⎣0 0 ⎦ ⎣1 0 ⎦ ⎣1 1⎦ ⎭⎪
⎡ a1 ⎤ ⎡ 1⎤
⎢ a ⎥ ⎢0 ⎥
⎡ 1 0⎤ ⎛ ⎡ 1 0⎤ ⎡ 1 1⎤ ⎡1 1⎤ ⎡1 1⎤ ⎞
id ⎢ ⎥ = ⎜⎜ a1 ⎢ ⎥ + a2 ⎢ ⎥ + a3 ⎢ ⎥ + a4 ⎢ ⎥ ⎟⎟ = 2⎥ = ⎢ ⎥

⎣0 0⎦ ⎝ ⎣0 0 ⎦ ⎣0 0⎦ ⎣1 0⎦ ⎣1 1⎦ ⎠c ⎢ a3 ⎥ ⎢0 ⎥
⎢ ⎥ ⎢ ⎥
⎣ a4 ⎦ ⎣ 0 ⎦

by inspection.
SECTION LT Linear Transformations 927

⎡ b1 ⎤ ⎡ −1⎤
⎢ ⎥ ⎢ ⎥
⎡0 1⎤ ⎛ ⎡ 1 0 ⎤ ⎡ 1 1⎤ ⎡1 1⎤ ⎡1 1⎤ ⎞ ⎢b2 ⎥ ⎢ 1⎥
id ⎢ ⎥ = ⎜⎜ b1 ⎢ ⎥ + b2 ⎢ ⎥ + b3 ⎢ + b4 ⎢ ⎥ ⎟⎟ = =
⎣0 0⎦ ⎝ ⎣0 0⎦ ⎣0 0⎦ ⎣1 0⎥⎦ ⎣1 1⎦ ⎠c ⎢ b3 ⎥ ⎢ 0 ⎥
⎢ ⎥ ⎢ ⎥
⎣b4 ⎦ ⎣ 0 ⎦
⎡ c1 ⎤ ⎡ 0 ⎤
⎢ ⎥ ⎢ ⎥
⎡0 0⎤ ⎛ ⎡ 1 0 ⎤ ⎡ 1 1⎤ ⎡1 1⎤ ⎡1 1⎤ ⎞ ⎢ c2 ⎥ ⎢ −1⎥
id ⎢ ⎥ = ⎜⎜ c1 ⎢ ⎥ + c2 ⎢ ⎥ + c3 ⎢ + c4 ⎢ ⎥ ⎟⎟ = =
⎣ 1 0⎦ ⎝ ⎣0 0⎦ ⎣0 0⎦ ⎣1 0 ⎥⎦ ⎣1 1⎦ ⎠c ⎢ c3 ⎥ ⎢ 1⎥
⎢ ⎥ ⎢ ⎥
⎣ c4 ⎦ ⎣ 0 ⎦
⎡ d1 ⎤ ⎡ 0 ⎤
⎢ ⎥ ⎢ ⎥
⎡0 0⎤ ⎛ ⎡ 1 0⎤ ⎡ 1 1⎤ ⎡1 1⎤ ⎡1 1⎤ ⎞ ⎢ d 2 ⎥ ⎢ 0 ⎥
id ⎢ ⎥ = ⎜⎜ d1 ⎢ ⎥ + d2 ⎢ ⎥ + d3 ⎢ + d4 ⎢ ⎥ ⎟⎟ = =
⎣0 1⎦ ⎝ ⎣0 0 ⎦ ⎣0 0⎦ ⎣1 0 ⎥⎦ ⎣1 1⎦ ⎠c ⎢ d3 ⎥ ⎢ −1⎥
⎢ ⎥ ⎢ ⎥
⎣ d 4 ⎦ ⎣ 1⎦

and
⎡ 1 −1 0 0 ⎤
⎢ 0 1 −1 0 ⎥
MB = ⎢ ⎥.
⎢ 0 0 1 −1⎥
⎢ ⎥
⎣ 0 0 0 1⎦

„ Associated Matrix Again


15. ( ) { }
T : P2 → R 3 where T at 2 + bt + c = ( a − b, a, 2c ) and B = t 2 , t , 1 as in Problem 8, but the
G G G G G
basis for R 3 is D = {e1 , e1 − e2 , 5e3 + e1} .

⎡ ⎡ 1⎤ ⎡ 1⎤ ⎡ 1⎤ ⎤ ⎡ a1 ⎤
⎡T t 2 ⎤ = [1 − 0, 1, 0] = ⎢ a1 ⎢ 0 ⎥ + a2 ⎢ −1⎥ + a3 ⎢ 0 ⎥ ⎥ = ⎢ a2 ⎥ ,
( )
⎣ ⎦D D ⎢ ⎢ ⎥ ⎢ ⎥ ⎢ ⎥⎥ ⎢ ⎥
⎢ ⎢⎣ 0 ⎥⎦ ⎢
⎣ ⎦0 ⎥ ⎢ ⎥
⎣ ⎦ ⎦ D ⎣ a3 ⎦⎥
5 ⎥ ⎢

1 = 1a1 + 1a2 + 1a3 , 1 = 0a1 − 1a2 + 0a3 , and 0 = 0a1 + 0a2 + 5a3 which yields the results
⎡ a1 ⎤ ⎡ 2 ⎤
⎢ a ⎥ = ⎢ −1⎥ .
⎢ 2⎥ ⎢ ⎥
⎢⎣ a3 ⎥⎦ ⎢⎣ 0 ⎥⎦

⎡ ⎡ 1⎤ ⎡ 1⎤ ⎡ 1⎤ ⎤ ⎡ b1 ⎤
⎢ ⎢ ⎥ ⎥
⎡⎣T ( t ) ⎤⎦ = [ −1, 0, 0]D = ⎢b1 ⎢ 0 ⎥ + b2 ⎢ −1⎥ + b3 ⎢ 0 ⎥ ⎥ = ⎢⎢b2 ⎥⎥ ,
⎢ ⎥ ⎢ ⎥
D
⎢ ⎢⎣ 0 ⎥⎦ ⎢⎣ 0 ⎥⎦ ⎢⎣ 5⎥⎦ ⎥⎦ ⎣⎢ b3 ⎦⎥
⎣ D

−1 = 1b1 + 1b2 + 1b3 , 0 = 0b1 − 1b2 + 0b3 , and 0 = 0b1 + 0b2 + 5b3 , which yields the results
⎡ b1 ⎤ ⎡ −1⎤
⎢b ⎥ = ⎢ 0 ⎥ .
⎢ 2⎥ ⎢ ⎥
⎢⎣ b3 ⎥⎦ ⎢⎣ 0 ⎥⎦
928 APPENDIX

⎡ ⎡ 1⎤ ⎡ 1⎤ ⎡ 1⎤ ⎤ ⎡ c1 ⎤
⎢ ⎢ ⎥ ⎥
⎡⎣T (1) ⎤⎦ = [ 0, 0, 2]D = ⎢ c1 ⎢ 0 ⎥ + c2 ⎢ −1⎥ + c3 ⎢ 0 ⎥ ⎥ = ⎢⎢ c2 ⎥⎥ ,
⎢ ⎥ ⎢ ⎥
D
⎢ ⎢⎣ 0 ⎥⎦ ⎢⎣ 0 ⎥⎦ ⎢⎣ 5⎥⎦ ⎥⎦ ⎢⎣ c3 ⎥⎦
⎣ D

0 = 1c1 + 1c2 + 1c3 , 0 = 0c1 − 1c2 + 0c3 , and 2 = 0c1 + 0c2 + 5c3 ,which yields the results

⎡ 2⎤

⎡ c1 ⎤ ⎢ 5 ⎥
⎢c ⎥ = ⎢ 0⎥
⎢ 2⎥ ⎢ ⎥
⎢⎣ c3 ⎥⎦ ⎢ 2 ⎥
⎢ ⎥
⎣ 5⎦

and
⎡ 2⎤
⎢ 2 −1 − 5 ⎥
⎢ ⎥
M ∗B = ⎢ −1 0 0⎥ .
⎢ 2⎥
⎢ 0 0 ⎥
⎣ 5⎦

„ Multiplying Associated Matrices

16. ( )
(a) T : P2 → R 3 where T at 2 + bt + c = ( a − b, a, 2c ) , as in Problem 8, but the basis for R 3 is
G G G G G
D = {e1 , e1 − e2 , 5e3 + e1} . Again from Problem 8 we see that

⎡ 1 −1 0 ⎤
M B = ⎢⎢ 1 0 0 ⎥⎥ .
⎢⎣ 0 0 2 ⎥⎦
G G G
We need to find M ∗c for the change of basis matrix from C = {e1 , e2 , e1} to basis D. We
determine the image vectors by inspection. 1 = a1 + a2 + a3 , 0 = − a2 , and 0 = 5a3 .

⎡ a1 ⎤ ⎡ 1⎤
G G G G G G G
e1 = ⎡⎣id ( e1 ) ⎤⎦ = ⎣⎡ a1e1 + a2 ( e1 − e2 ) + a3 ( 5e3 + e1 ) ⎦⎤ = ⎢⎢ a2 ⎥⎥ = ⎢⎢0 ⎥⎥
D D
⎢⎣ a3 ⎥⎦ ⎢⎣0 ⎥⎦
⎡ b1 ⎤ ⎡ 1⎤
G G G G G G G
e2 = ⎡⎣id ( e2 ) ⎤⎦ = ⎣⎡b1e1 + b2 ( e1 − e2 ) + b3 ( 5e3 + e1 ) ⎦⎤ = ⎢⎢b2 ⎥⎥ = ⎢⎢ −1⎥⎥
D D
⎢⎣ b3 ⎥⎦ ⎢⎣ 0 ⎥⎦
⎡ 1⎤

⎡ c1 ⎤ ⎢ 5 ⎥
G G G G G G G ⎢ ⎥
e3 = ⎡⎣id ( e3 ) ⎤⎦ = ⎡⎣c1e1 + c2 ( e1 − e2 ) + c3 ( 5e3 + e1 ) ⎤⎦ = ⎢⎢c2 ⎥⎥ = ⎢ 0 ⎥
D D
⎢⎣ c3 ⎥⎦ ⎢ 1 ⎥
⎢ ⎥
⎣ 5⎦
SECTION LT Linear Transformations 929

and
⎡ 1⎤
⎢1 1 − 5⎥
⎢ ⎥
M ∗C = ⎢0 −1 0⎥ .
⎢ 1⎥
⎢0 0 ⎥
⎣ 5⎦

⎡ 1⎤ ⎡ 2⎤
⎢ 1 1 − 5 ⎥ ⎡ 1 −1 0 ⎤ ⎢ 2 −1 − 5 ⎥
⎢ ⎥ ⎢ ⎥
(b) The required matrix is M ∗B = M ∗C M B = ⎢ 0 −1 0 ⎥ ⎢⎢ 1 0 0 ⎥⎥ = ⎢ −1 0 0⎥ .
⎢ 1 ⎥ ⎢⎣0 0 2 ⎥⎦ ⎢ 2⎥
⎢0 0 ⎥ ⎢ 0 0 ⎥
⎣ 5⎦ ⎣ 5⎦
930 APPENDIX

PF Partial Fractions

„ Practice Makes Perfect


1
1. . We write this fraction in the form
x ( x − 1)

1 A B
= + .
x ( x − 1) x x − 1

Clearing fractions, we get


1 = A ( x − 1) + Bx .

Collecting terms yields


( A + B) x − A = 1 .
Equating coefficients yields the equations
A+ B = 0
−A =1

which has the solutions A = −1 and B = 1 . Hence, we have


1 −1 1
= + .
x ( x − 1) x x − 1

1
2. . We write this fraction in the form
( x + 2 )( x − 1)
1 A B
= + .
( x + 2 )( x − 1) x + 2 x −1

Clearing of fractions yields


1 = A ( x − 1) + B ( x + 2 ) .

Collecting terms yields


( A + B ) x + ( − A + 2 B − 1) = 0 .
1 1
Equating coefficients and solving we find A = − and B = . Hence, we have the partial
3 3
fraction decomposition
1 1 1 1 1
=− + .
( x + 2 )( x − 1) 3 x + 2 3 x −1
SECTION PF Partial Fractions 931

x
3. . We write this fraction in the form
( x + 1)( x + 2 )
x A B
= + .
( x + 1)( x + 2 ) x +1 x + 2

Clearing of fractions yields


x = A ( x + 2 ) + B ( x + 1) .

Collecting terms yields


( A + B − 1) x + ( 2 A + B ) = 0 .
Equating coefficients we find the equations
A + B =1
2A + B = 0

which has the solutions A = −1 and B = 2 . Hence, yielding


x −1 2
= + .
( )(
x + 1 x + 2 ) x + 1 x + 2

x
4. . Write this fraction in the form
(x 2
)
+ 1 ( x − 1)

x Ax + B C
= + .
(x 2
)
+ 1 ( x − 1) x +1 x −1
2

Clearing of fractions yields

x = ( Ax + B )( x − 1) + C x 2 + 1 .( )
Collecting terms yields

( A + C ) x 2 + ( − A + B − 1) x + ( C − B ) = 0 .
Equating coefficients we find the equations
A+C =0
−A + B =1
−B + C = 0
1 1
which has the solutions A = − and B = C = . Hence we have
2 2
x 1 x −1 1 1
=− + .
(x 2
)
+ 1 ( x − 1) 2 x2 + 1 2 x − 1
932 APPENDIX

4
5. . We write this fraction in the form
x 2
(x 2
+4 )
4 A B Cx + D
= + + .
x 2
(x 2
+4 ) x x2 x2 + 4

Clearing of fractions yields


4 = ( A + C ) x3 + ( B + D ) x 2 + 4 Ax + 4 B .

Equating coefficients and solving we find A = 0 , B = 1 , C = 0 , and D = −1 . Hence, we have the


partial fraction decomposition
4 1 1
= − 2 .
x 2
(x 2
+4 ) x 2
x +4

3
6. . We write this fraction in the form
(x 2
)(
+ 1 x2 + 4 )
3 Ax + B Cx + D
= + 2 .
(x 2
+1 x + 4)( 2
) x2 + 1 x +4

Clearing of fractions yields


3 = ( A + C ) x3 + ( B + D ) x 2 + ( 4 A + C ) x + 4 B + D .

Equating coefficients and solving we find A = 0 , B = 1 , C = 0 , and D = −1 . Hence, yielding the


partial fraction decomposition
3 1 1
= − 2 .
(x 2
+1 x + 4)( 2
) 2
x +1 x + 4

7x −1
7. . We write this fraction in the form
( )( x + 2 )( x − 3)
x + 1

7x −1 A B C
= + + .
( x + 1)( x + 2 )( x − 3) x + 1 x + 2 x − 3
Clearing of fractions, yields
7 x − 1 = A ( x + 2 )( x − 3) + B ( x + 1)( x − 3) + C ( x + 1)( x + 2 ) .

Equating coefficients we find

( A + B + C ) x 2 + ( − A − 2 B + 3C − 7 ) x + ( −6 A − 3B + 2C + 1) = 0 .
Solving this equation we find the solutions A = 2 , B = −3 , and C = 1 . Hence, we have the partial
fraction decomposition
7x −1 2 3 1
= − + .
( )(
x + 1 x + 2 )( )
x − 3 x + 1 x + 2 x −3
SECTION PF Partial Fractions 933

x2 − 2
8. . We write this fraction in the form
x ( x + 7 )( x + 1)

x2 − 2 A B C
= + + .
x ( x + 7 )( x + 1) x x + 7 x + 1

Clearing of fractions yields


x 2 − 2 = A ( x + 7 )( x + 1) + Bx ( x + 1) + Cx ( x + 7 ) .

Equating coefficients we find

( A + B + C − 1) x 2 + (8 A + B + 7C ) x + ( 7 A + 2 ) = 0 .
2 47 1
Solving this equation we find A = − , B = , and C = . Hence, yielding the partial fraction
7 42 6
decomposition
x2 − 2 2 47 1 1 1
=− + + .
x ( x + 7 )( x + 1) 7 x 42 x + 7 6 x + 1

x2 + 9 x + 2
9. . We write this fraction in the form
( x − 1) ( x + 3)
2

x2 + 9 x + 2 A B C
= + + .
( x − 1) ( x + 3)
2
x − 1 ( x − 1) 2
x+3

Clearing of fractions yields

x 2 + 9 x + 2 = A ( x − 1)( x + 3) + B ( x + 3) + C ( x − 1) .
2

Equating coefficients we find

( A + C − 1) x 2 + ( 2 A + B − 2C − 9 ) x + ( −3 A + 3B + C − 2 ) = 0 .
Setting the coefficients equal yields
A + C −1 = 0
2 A + B − 2C = 9
−3 A + 3B + C = 2.

Solving these equations we find A = 2 , B = 3 , and C = −1 . Hence we have the partial fraction
decomposition
x2 + 9 x + 2 2 3 1
= + − .
( x − 1) ( x + 3) x − 1 ( x − 1) x+3
2 2
934 APPENDIX

x2 + 1
10. . We write this fraction in the form
x3 − 2 x 2 − 8 x

x2 + 1 x2 + 1 A B C
= = + + .
x − 2 x − 8 x x ( x + 2 )( x − 4 ) x x + 2 x − 4
3 2

Clearing of fractions yields


x 2 + 1 = A ( x + 2 )( x − 4 ) + Bx ( x − 4 ) + Cx ( x + 2 ) .

Equating coefficients we find

( A + B + C − 1) x 2 + ( −2 A − 4 B + 2C ) x + ( −8 A − 1) = 0 .
1 5 17
Solving this equation yields the solutions A = − , B = , and C = . Hence we have the
8 12 24
partial fraction decomposition
x2 + 1 1 5 1 17 1
=− + + .
3 2
x − 2 x − 8x 8 x 12 x + 2 24 x − 4